An Efficient One‐Pot Synthesis of Chiral N‐Protected 3‐Substituted (Diketo)piperazines via Ugi‐4CR/De‐Boc/Cyclization Process. Issue 4 (25th January 2018) - Jida, Mouhamad; Ballet, Steven
Abstract: A convenient and high yielding method to prepare a vast array of enantiomerically pure 3‐substituted diketopiperazines (3‐DKPs), bearing a benzyl protecting group on nitrogen 1 is reported. The methodology describes a simple one‐pot procedure, starting from readily available N‐protected L‐ or D‐amino acids employing the Ugi‐4CR in pure water, followed by a one‐step Boc‐deprotection and final lactamisation in acetic acid. All disubstituted DKPs were obtained in short times and isolated in excellent yields (84‐94%) by simple precipitation in water and subsequent filtration. The practical utility of this procedure proved efficient for the synthesis of cialis (Tadalafil) analogues. Abstract : A simple and green one‐pot strategy is developed to access a library of chiral N ‐protected‐ 3‐substituted (diketo)piperazines in excellent yields and high enantioselectivity. The methodology describes a simple one‐pot procedure, starting from readily available N‐protected L‐ or D‐amino acids employing the Ugi‐4CR in pure water, followed by a one‐step Boc‐deprotection and final lactamisation in acetic acid. The practical utility of this procedure proved efficient for the synthesis of cialis (Tadalafil) analogues.